Design and implementation of an efficient model for the transformation and use of organic solid urban waste - Vasquez Aguilar, Yasira Helena; Ruiz Martínez, Lida Esperanza; Serna Caicedo, Jesús Alberto (Ingeniería Solidaria, 2022)
Introduction: This article is the development of the "Design and implementation of an efficient model for the transformation and use of organic solid waste", in the “El Conjunto Residencial de Ontario in Bogotá. (Colombia)”. Problem: The accumulation of solid urban waste by the residential community shows an environmental problem that results in health problems, bad odors, the attraction of rodents and a poor physical appearance in the common areas of this complex, caused by the lack of use of this organic waste. Objective: formulate an efficient model for the transformation and use of organic solid waste in the “Conjunto Residencial Tejar de Ontario”. Methodology: Characterization by the method of quartering and use of organic waste through the design of a micro composting plant. Results: Physical properties such as color, odor and texture are recognized as well as chemical parameters such as C / N, pH and humidity, with these tools we obtain a good quality and fertile compost. Conclusion: The transformation of urban organic solid waste is an effective way of mitigating the environmental impact caused by not using it and simultaneously preventing this waste from reaching landfills. Originality: This transformation and use design was carried out for the first time in the “Conjunto Residencial Tejar de Ontario”, it also contains management strategies that allow optimizing the composting operation. Limitations: Find tools that are easily understood by the community to strengthen knowledge of recycling, source separation and composting.
Keywords: characterization; Bogotá; organic; set; waste; domestic; exploitation